2020
DOI: 10.7150/ijbs.38431
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of brain-expressed X-linked 2 (BEX2) promotes colorectal cancer metastasis through the Hedgehog signaling pathway

Abstract: The incidence of colorectal cancer is increasing, and cancer metastasis is one of the major causes of poor outcomes. BEX2 has been reported to be involved in tumor development in several types of cancer, but its role in metastatic colorectal cancer remains largely undefined. Herein, we demonstrated that BEX2 knockout resulted in enhanced migratory and metastatic potential in colorectal cancer cells both in vitro and in vivo, and re-expression of BEX2 in knockout cells could reverse the enhanced migratory capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Numerous studies have demonstrated that aberrant Gli1 expression in Hedgehog pathway plays a critical role in the development of CRC [ 20 , 26 ] and Gli1 promotes EMT in CRC cells [ 27 , 28 ]. Thus, we speculated whether Gli1 is regulated by AIM2 in CRC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that aberrant Gli1 expression in Hedgehog pathway plays a critical role in the development of CRC [ 20 , 26 ] and Gli1 promotes EMT in CRC cells [ 27 , 28 ]. Thus, we speculated whether Gli1 is regulated by AIM2 in CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The Hedgehog (Hh) signaling pathway plays an essential role in cancer development and progression [ 19 , 20 ]. Gli1, as a key transcriptional factor of Hh pathway, has been proposed as a candidate oncogene in CRC [ 20 , 26 , 27 ]. In the present study, we found that AIM2 regulated Gli1 expression in CRC cells, which is evidenced by the following observations.…”
Section: Discussionmentioning
confidence: 99%
“…The brain expressed X‐linked genes are included in a group of genes that reside on the X‐chromosome with clustering and related to transcriptional regulation and signaling pathways in neurodegeneration, cell cycle and tumor growth 19 . Especially, BEX2 is included in the regulation of the transcriptional activity of oligomeric DNA binding complex containing LMO2 and NSCL2 20 .…”
Section: Discussionmentioning
confidence: 99%
“…An RNA-seq data set of DLD-1 colorectal cancer cells (SRR6929326) was download from the sequence read archive (SRA), which contain 48.8 million paired short reads (150 bp). The RNA sample was prepared using the Illumina TruSeq RNA Sample Preparation protocol and deeply sequenced with an Illumina HiSeq 3000 42 . Phred quality scores (Q score) reported by FastQC (version 0.11.8) 43 showed that more than 90% of the short reads reached Q30 (99.9% base call accuracy).…”
Section: Data Setsmentioning
confidence: 99%